2019
DOI: 10.1039/c9qo00191c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of aryl and heteroaryl tetrafluoro-λ6-sulfanyl chlorides from diaryl disulfides using trichloroisocyanuric acid and potassium fluoride

Abstract: A catalyst-free method for the synthesis of (Het)ArSF4Cl by using trichloroisocyanuric acid and potassium fluoride in acetonitrile is disclosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…More and more examples of biologically active SF 5 -containing drug candidates have been reported in recent years (Figure 1c) [35,38,39,40,41,42,43,44]. Extending our research to the design and synthesis of SF 5 -containing biologically attractive molecules [45,46,47,48,49,50,51,52,53,54,55,56,57] and a halogen bonding research program [58,59], we are interested in aryl iodides 1a – d consisting of SF 5 -group(s) in the benzene ring as potential drug fragments capable of halogen bonding, in particular, 3,5-bis-SF 5 -iodobenzene ( 1d , Figure 1d). In this research, we have examined the halogen bonding induced by SF 5 -aryl iodides 1a – d .…”
Section: Introductionmentioning
confidence: 80%
“…More and more examples of biologically active SF 5 -containing drug candidates have been reported in recent years (Figure 1c) [35,38,39,40,41,42,43,44]. Extending our research to the design and synthesis of SF 5 -containing biologically attractive molecules [45,46,47,48,49,50,51,52,53,54,55,56,57] and a halogen bonding research program [58,59], we are interested in aryl iodides 1a – d consisting of SF 5 -group(s) in the benzene ring as potential drug fragments capable of halogen bonding, in particular, 3,5-bis-SF 5 -iodobenzene ( 1d , Figure 1d). In this research, we have examined the halogen bonding induced by SF 5 -aryl iodides 1a – d .…”
Section: Introductionmentioning
confidence: 80%
“…A very similar methodology -albeit in the absence of TFA and using 20 equiv. of both TCICA and KF, with longer reaction times (48 h) -was reported later in the same year by Shibata et al 14 An analytical-scale synthesis of ArSF4Cl using flow microfluidic technology, exploiting the conditions described first by Togni and subsequently by Shibata (TCICA in acetonitrile, KF on a column), was reported to produce low yields (up to 11%) of the target compounds. 15 Attempts to produce the corresponding SF5compounds were unsuccessful.…”
Section: Template For Synthesis Thiemementioning
confidence: 78%
“…To develop a synthetically useful method in common research laboratories, we optimized Togni's procedure (Scheme 1). It was found that the catalytic amounts of TFA was not necessary for the formation of SF 5 Cl, [6e] and the protection from light is crucial for this reaction. The reaction of sulfur powder, dry KF, and TCCA in MeCN under light only afforded the byproducts SO 2 F 2 and SOF 2 , whereas SF 5 Cl was formed in the absence of light along with SO 2 F 2 and SOF 2 .…”
Section: Methodsmentioning
confidence: 99%